The Economics of Subsidising Agriculture A Study of British Policy - McCrone, Gavin (University of Toronto Press, 2019)
This is a study of British agricultural policy since the war -- during a period which has seen the adoption of a comprehensive system of agricultural support which has seen the adoption of a comprehensive system of agricultural support which stands in marked contrast to the free trade policy adhered to for so long in the past. The policy of support has brought a substantial increase in the output of British agriculture, but it has imposed a heavy burden on the taxpayer and has often been the subject of controversy. Mr. McCrone considers the economic issues involved: he sets out the implications of the present policy and compares the role of agriculture in Britain with the part it plays in other countries; he analyses the contribution of agriculture to the balance of payments and considers the prospects for Britain's imported food supplies. This involved an analysis of the main sources of Britain's food supply and the likely effects of economic development both on the exporting countries and on other potential food importers. The effects of the European Common Market are considered and the British system of support is contrasted with that used in other European countries. The book concludes with an assessment of the prospects for British agriculture and the part required of it in the national economy
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Nov 2019)
Keywords: BUSINESS & ECONOMICS / Industries / Agribusiness